The architecture of exhibitions : experiential design - Melis, Alessandro; Vavetsi, Rozina; Finotti, Fabio (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"The Architecture of Exhibitions embarks on a comprehensive exploration of creativity and design innovation within exhibition spaces. It describes the fundamental principles of exhibition design, tracing the origins of creativity and considering its evolutionary significance. The book challenges conventional boundaries imposed by rigid classifications, drawing on heuristic studies in biology and the transformative concept of exaptation. It questions the traditional separations between art, science, and technology, which often hinder innovation. By advocating for an interdisciplinary approach, it reimagines creativity that transcends conventional limits. Through practice-based research, multidisciplinary case studies, and technological innovations, with a focus on Generative AI, the book illustrates how modern exhibition spaces actively engage with their audiences, highlighting their profound impact beyond academic discourse. This book is designed for curators, designers, and scholars who are passionate about the future of exhibition spaces. It offers a comprehensive understanding through its four-part structure, making it an essential read for anyone interested in the dynamic interplay between art, technology, and society. The book is also designed as an instrument for the education of architecture, design, and art students"--
Meta-exhibition designs / Anthony Caradonna -- Stereoma : creating an immersive spatial experience / Dustin White -- Enhancing the sense of place through performative arts : the case of Venice / Jose Antonio Lara-Hernandez.
Keywords: Space (Architecture) -- Psychological aspects; Art -- Exhibition techniques; Art and technology; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting